Visual-spatial cognition in children using aided communication. (2nd January 2018) - Stadskleiv, Kristine; Batorowicz, Beata; Massaro, Munique; van Balkom, Hans; von Tetzchner, Stephen
Abstract: Children with severe motor impairments are restricted in their manipulation and exploration of objects, but little is known about how such limitations influence cognitive development. This study investigated visual-constructional abilities in 75 children and adolescents, aged 5;0–15;11 (years;months), with severe speech impairments and no intellectual disabilities (aided group) and in 56 children and adolescents with typical development (reference group). Verbal comprehension, non-verbal reasoning, and visual-spatial perception were assessed with standardized tests. The task of the participants was to verbally instruct communication partners to make physical constructions identical to models that the partner could not see. In the aided group, 55.7% of the constructions were identical to the models participants described, compared to 91.3% in the reference group. In the aided group, test results explained 51.4% of the variance in construction errors. The results indicate that the participants' language skills were decisive for construction success. Visual-perceptual challenges were common among the aided communicators, and their instructions included little information about size and spatial relations. This may reflect less experience with object manipulation and construction than children with typical development, and using aided communication to instruct others to make three-dimensional constructions. The results imply a need for interventions that compensate for the lack of relevant experience.